(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
This investigation deals with studying the parameters affecting coagulation-flocculation behaviour such as coagulant types, dosage and settling time; the results show reduction in COD, TSS, and adjusted pH value using lime with magnesium chloride and alum. Final results revealed that percent removal of COD 93.3%, percent removal of TSS 92.8% and pH is 8. Better coagulation performance which resulted best COD and TSS removal was acheived using 1g/L CaO with 1 g/L MgCl2.7H2O and 250 mg/L Al2(SO4)3. In this paper also then effect of intensity and time of mixing was studied. Finally a treatment process steps were designed and a process flow diagram for the treatment plant was illustrated